Spiro-fused carbohydrate oxazoline ligands: Synthesis and application as enantio-discrimination agents in asymmetric allylic alkylation - Kraft, Jochen (Beilstein J Org Chem, 2016)
In the present work, we describe a convenient synthesis of spiro-fused D-fructo- and D-psico-configurated oxazoline ligands and their application in asymmetric catalysis. The ligands were synthesized from readily available 3,4,5-tri-O-benzyl-1,2-O-isopropylidene-β-D-fructopyranose and 3,4,5-tri-O-benzyl-1,2-O-isopropylidene-β-D-psicopyranose, respectively. The latter compounds were partially deprotected under acidic conditions followed by condensation with thiocyanic acid to give an anomeric mixture of the corresponding 1,3-oxazolidine-2-thiones. The anomeric 1,3-oxazolidine-2-thiones were separated after successive benzylation, fully characterized and subjected to palladium catalyzed Suzuki–Miyaura coupling with 2-pyridineboronic acid N-phenyldiethanolamine ester to give the corresponding 2-pyridyl spiro-oxazoline (PyOx) ligands. The spiro-oxazoline ligands showed high asymmetric induction (up to 93% ee) when applied as chiral ligands in palladium-catalyzed allylic alkylation of 1,3-diphenylallyl acetate with dimethyl malonate. The D-fructo-PyOx ligand provided mainly the (R)-enantiomer while the D-psico-configurated ligand gave the (S)-enantiomer with a lower enantiomeric excess.